Modification of Photosystem I Light Harvesting of Bundle-Sheath Chloroplasts Occurred during the Evolution of NADP-Malic Enzyme C4 Photosynthesis. - Pfundel, E. (1997)
Low-temperature emission spectra and excitation spectra for chlorophyll fluorescence were recorded from leaves of species of the genus Flaveria (Asteraceae) with C3, C3-C4-intermediate, C4-like, and C4 photosynthesis. Among the latter two groups, high chlorophyll b absorption was observed in excitation spectra for photosystem I (PSI) fluorescence. By comparing leaf data with those from isolated chloroplast fractions, the high chlorophyll b absorption was attributed to the specific properties of the bundle-sheath chloroplasts in leaves from C4 plants. The deconvolution of the PSI excitation spectra and the use of a model revealed that the contribution of photosystem II absorption to the functional antenna of PSI was markedly increased in leaves from three of the five C4-like and C4 species investigated in detail. The two other species exhibited normal, C3-like light-harvesting properties of PSI. The former species are known for efficient carbon assimilation, the latter for decreased efficiencies of carbon assimilation. It is concluded that photosystem II becomes a substantial part of the functional PSI antenna late in the evolution of C4 photosynthesis, and that the composite antenna optimizes the light-harvesting of PSI in bundle-sheath chloroplasts to meet the energy requirements of C4 photosynthesis.